Analisis Pengalaman Belajar Siswa melalui Eksperimen Gunung Meletus Buatan dalam Memahami Konsep Perubahan Wujud Benda di MI Miftahul Ulum - Muhammad Suwigyo Prayogo; Rezawati Rohmah; Avini Rahmi Ramadani (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
This study focuses on the analysis of students' learning experiences through artificial volcanic eruption experiments in understanding the material of changes in the state of matter at MI Miftahul Ulum. The problem underlying this study is the difficulty students have in learning the abstract concept of changes in state, so a learning strategy based on real experiences is needed. The artificial volcanic eruption experiment was chosen because it is able to show the process of changes in the state of matter through simple chemical reactions in an interesting and easy-to-understand way. The method used is qualitative research with a descriptive approach. The subjects of the study were fifth-grade students of MI Miftahul Ulum. Data were obtained through observation, interviews, and documentation, then analyzed using the stages of data reduction, data presentation, and drawing conclusions. The results of the study showed that the implementation of the artificial volcanic eruption experiment created a meaningful learning experience for students. Students appeared more enthusiastic, active, and easily grasped the concept of changes in the state of matter because they experienced the change process directly. In addition, this experiment also fostered students' curiosity, cooperation, and scientific attitudes in learning activities. Based on these findings, it can be concluded that the artificial volcanic eruption experiment is an effective learning medium to strengthen the learning experience while improving students' understanding of the material of changes in the state of matter.